2013
DOI: 10.1007/s10291-013-0355-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GPS + Galileo and multi-frequency Galileo single-epoch precise positioning with network corrections

Abstract: Several processing strategies that use dual-frequency GPS-only solution, multi-frequency Galileo-only solution, and finally tightly combined dual-frequency GPS ? Galileo solution were tested and analyzed for their applicability to single-epoch long-range precise positioning. In particular, a multi-system GPS ? Galileo solution was compared to GPS double-frequency solution as well as to Galileo double-, triple-, and quadruple-frequency solutions. Also, the performance of the strategies was analyzed under clear-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 29 publications
0
57
0
Order By: Relevance
“…Several contributions were devoted not only to algorithm development and assessment [26,32], but also to characterisation of the inter GPS-Galileo system biases both in precise relative (RTK) and absolute methods (PPP) [33][34][35][36][37]. Thus, the RTK method can be considered as under extensive development and being used for a growing number of applications.…”
Section: Gsat0201 (5-mentioning
confidence: 99%
See 1 more Smart Citation
“…Several contributions were devoted not only to algorithm development and assessment [26,32], but also to characterisation of the inter GPS-Galileo system biases both in precise relative (RTK) and absolute methods (PPP) [33][34][35][36][37]. Thus, the RTK method can be considered as under extensive development and being used for a growing number of applications.…”
Section: Gsat0201 (5-mentioning
confidence: 99%
“…The relative positioning model based on geometry with parameterised ionospheric delays is given in Equation (5). The equations are presented for dual frequency phase and code observables; however, the model may be extended for multi-frequency signals accordingly [32]:…”
Section: Loosely Combined Relative Positioning Model With Parameterismentioning
confidence: 99%
“…The initial research was conducted by Teunissen (1997) and Odijk (2000a, b). Since the details may be found in several publications (Julien et al 2004;Wielgosz 2010;Paziewski and Wielgosz 2014), only a brief description is presented here.…”
Section: Functional Model Of Precise Positioningmentioning
confidence: 99%
“…Therefore, the scientific community has put extensive effort into the development of new algorithms for ionospheric delay mitigation in precise rapid positioning. These advances have led to the development of a geometry-based ionosphere-weighted model supported with network-derived ionospheric corrections (Teunissen 1997;Odijk 2000a, b;Julien et al 2004;Hu et al 2005;Wielgosz 2010;Paziewski and Wielgosz 2014). This approach, often performed in the multi-baseline mode, allows reliable positioning even up to several tens of kilometers.…”
Section: Introductionmentioning
confidence: 99%
“…As well, Odijk and Teunissen (2013) showed that prior correction of the differential GPS/Galileo (GIOVE) inter-system biases significantly increases the success rate of instantaneous ambiguity resolution for short baselines. Likewise, Paziewski and Wielgosz (2013) showed that combining GPS/Galileo observables in a double-differenced carrier-phase and pseudorange technique improves the success rate of instantaneous ambiguity resolution in comparison with GPS-only solution. Unfortunately, however, their work was limited to differential positioning techniques.…”
Section: Introductionmentioning
confidence: 99%